ANALISIS PENGARUH TEKNOLOGI ARTIFICIAL INTELLIGENCE (AI) DALAM PROSES SELEKSI DAN REKRUTMEN MSDM: SYSTEMATIC LITERATURE REVIEW - Reszia Nurul Febri Diani; Nurul Sulistianingsih; Pinky Flora Eka Tantri; Dani Rizana (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to examine the Influence of AI Technology in the HR Selection and Recruitment Process. The method used in the Systematic Literature Review (SLR) study, which involves collecting data and information from related literature, such as journals, internet articles, etc. To gain a better understanding of the influence that occurs on the topic discussed, this study analyzes previous relevant research. The results of the study indicate that Artificial Intelligence (AI) technology has a significant influence on the human resource management (HR) selection and recruitment process. AI can improve efficiency, accuracy, and objectivity in the process, but also presents challenges such as potential algorithmic bias and impact on the experience of prospective employees. Therefore, it is important for organizations to develop ethical policies and provide adequate training to staff to maximize the benefits of using AI. This study aims to examine the Influence of AI Technology in the HR Selection and Recruitment Process. The method used in the Systematic Literature Review (SLR) study, which involves collecting data and information from related literature, such as journals, internet articles, etc. To gain a better understanding of the influence that occurs on the topic discussed, this study analyzes previous relevant research. The results of the study show that Artificial Intelligence (AI) technology has a significant impact on the selection and recruitment process of human resource management (HRM). AI can improve efficiency, accuracy, and objectivity in the process, but also presents challenges such as potential algorithmic bias and impact on the experience of prospective employees. Therefore, it is important for organizations to develop ethical policies and provide adequate training to staff to maximize the benefits of using AI.